Espectro da doença hepático-gordurosa não alcoólica em obesos mórbidos : prevalência e fatores associados - Fernandes, Suerda (2005)
Non-alcoholic fatty liver disease (NAFLD) became a challenge for everyone who is devoted to study liver diseases. The multifactorial etiopathogenesis, not totally explained yet, the lack of consensus around the terminology, classification and treatment, especially in the morbidly obese group, are a few of some aspects that could be cited to justify the growing interest. Since the beginning, obesity has been said to be an important factor associated to the development of NAFLD. In fact, it is an important point since obesity has become a problem of great concern all over the world. It was determined the prevalence of NAFLD and non-alcoholic steatohepatitis (NASH), in a sample of morbidly obese patients, who underwent surgical gastroplasty, in whom other causes of liver disease were excluded. The aim was yet, to identify demographic, anthropometric and laboratorial factors associated with the spectrum of the disease. The study shows a high prevalence of NAFLD, 95% (57/60). Steatosis was used as a minimum criterion to the histopathologic diagnosis of NAFLD and NASH demands the presence of steatosis, lobular inflammation and hepatocellular ballooning as found minimally, to the histologic diagnosis. We found that the prevalence of NASH, was particularly elevated in the studied group, 66,7% (40/60). However, it was observed mild grade in 80% (32/40) of the cases of NASH. Fibrosis staging was only seen in 7,5% (3/40) of the NASH sample and cirrhosis was not found in any particular patient. The following parameters were associated with steatosis degree in univariate analysis: age, metabolic syndrome, waist circumference, HDL-C (inversely), triglycerides, ALT, GGT and serum ferritin. After submitting these variables at the logistic regression analysis, only GGT was significantly e independently associated with steatosis degree. The following categorical and continuous variables were associated with NASH in univariate analysis: diabetes combined with raised fasting plasma glucose; triglycerides and ALT. Using logistic regression none of these variations remained significant. In summary, it was found a high prevalence of NAFLD, and, specifically, a high prevalence of NASH in this population of morbidly obese patients. Since NASH patients are at major risk of progressing to cirrhosis, liver biopsy must be performed as a routine part of the operative procedure to access prognostic information and to select patients that may benefit from inclusion in therapeutic protocols treatments. As an extent careful hepatic clinical follow up for all this group is advisable.